A Teaching Framework for Using Austerity Media Discourse in Large EAP classrooms - Wiranegara, Dian Arsitades; Basori, Muchamad Adam (Journal of English for Academic and Specific Purposes (JEASP), 2025)
This study proposes a pedagogical framework for integrating media discourse into English for Academic Purposes (EAP) instruction in large classes, grounded in Entman’s framing theory and Van Dijk’s critical discourse analysis. Using authentic texts on Indonesia’s austerity policy—specifically, the suspension of civil servants’ 13th and 14th salaries—the framework enhances students’ academic literacy, rhetorical awareness, and critical thinking. Over six weeks, learners engaged in discourse-analysis tasks, small-group discussions, and digital collaboration (e.g., Quizizz, Google Docs). Instruction focused on identifying framing elements (e.g., problem, cause, evaluation, solution) and linguistic features (e.g., modality, evaluative language, passive voice) to show how language shapes ideology. Data from reflections, discussions, field notes, and assignments were thematically analyzed. Findings showed students gained critical awareness of bias, expanded academic vocabulary, and improved syntactic control (e.g., nominalizations, passives). They also demonstrated stronger argumentation and rhetorical organization in essays and debates. The study presents a replicable model for critical, technology-enhanced EAP instruction that supports multilingual learners in higher education